Eksplorasi Penggunaan Keberlanjutan Sistem Informasi pada Pengguna Virtual Account - Putri, Nikki Ananda; Bharata, Wira (Penerbit Goodwood, 2025)
Purpose: This study examined the sustainable use of an information system using the IS Continuance and Technology Acceptance Model (TAM) as a theory.Methodology/Approach: This is a quantitative research study with an explanatory method. The respondents are virtual account users on the Shopee in Samarinda City. Data were collected using purposive sampling and Structural Equation Model (SEM) techniques with SmartPLS.Results/Findings: The test results showed Perceived Ease of Use has a positive and significant impact on Attitude, Perceived Usefulness has a positive and significant impact on Attitude, Attitude has a positive and significant impact on IS Continuance, Perceived Ease of Use has a positive and significant impact on IS Continuance, and Perceived Usefulness has a positive and significant effect on IS Continuance. In addition, there is also a positive and significant effect of Attitude in mediating the relationship between Perceived Ease of Use on IS Continuance and Perceived Usefulness on IS Continuance. Conclusions: Perceived Ease of Use has a positive and significant effect on Attitude; Perceived Usefulness has a positive and significant effect on Attitude; Attitude has a positive and significant effect on IS Continuance; Perceived Ease of Use has a positive and significant effect on IS Continuance; Perceived Usefulness has a positive and significant effect on IS Continuance. Attitude was also found to be able to mediate the relationship between Perceived Ease of Use and IS Continuance positively and significantly, and also mediate the relationship between Perceived Usefulness and IS Continuance positively and significantly.Limitations: The variable in IS Continuance Theory are not used in their entirety, but only limited to aspects that improve customer attitudes, and create continuance information system usage actions. Contribution: The research focuses on the act of sustainable use carried out by information system users. The goal is to improve facilities that support uses convenience and usability so that users can show a positive attitude which will create information system continuance.